Hierarchical extreme learning machine for body part detector - Lim, Zhong Hui (2016)
In the recent years, body part detection had gain significant interest and popular because of the capability of its impact towards understanding human behavior under distinctive circumstances. Estimating and marking of human body parts of different posture in videos or pictures give fundamental insights for breaking down human conduct and activities. Nevertheless, Human body exhibits huge amount of variation in an image due to variation in posture, viewing angle etc making body part detection very difficult.